9C.08: HEART RATE AS A PREDICTOR OF CARDIOVASCULAR OUTCOMES. (June 2015) - Meredith, P.; Elliott, H.L.
Abstract : Objective: Received wisdom suggests that treatments which reduce heart rate (HR), or avoid cardio-acceleration, are associated with improved cardiovascular (CV) outcomes. However, in the SIGNIFY trial in 12, 049 patients with symptomatic angina, a sub-group analysis demonstrated a small but significant increase in the combined risk of CV death or non-fatal MI with the new anti-anginal agent, ivabradine, which is designed to reduce heart rate. The safety and efficacy of the long-acting calcium channel blocker, Nifedipine GITS (an established anti-anginal agent) has been confirmed via the positive results in the placebo-controlled ACTION trial in patients with stable symptomatic coronary artery disease (CAD). This further, retrospective analysis of the ACTION database has evaluated the inter-relationships between baseline HR, and its on-treatment changes, on subsequent cardiovascular outcomes. Design and method: The retrospective analyses of the ACTION trial were performed for quintiles of HR, using the multivariate Cox proportional hazard model, for baseline HR and the achieved HR after 6 weeks of the trial (by which time titration of both placebo and nifedipine GITS was complete). Results: For baseline HR, the risk in the lowest (<56 bpm) was significantly reduced when compared to the highest quintile (HR > 72BPM) for the primary trial endpoint (HR = 0.81 CI 0.70, 0.94); any cardiovascular (CV) event (HR = 0.82 CI 0.70, 0.96); and new onset heart failure (HR = 0.48 CI 0.31, 0.74). No significant differences were apparent for myocardial infarction (MI) or debilitating stroke. In contrast, there was no evidence that on-treatment HR was predictive of outcome: for example, for the primary efficacy endpoint (any CV event, HF, MI and debilitating stroke) the event rates were similar across the quintiles of HR. Correspondingly, there was no significant HR-related treatment effect (comparing nifedipine GITS and placebo). Conclusions: Whilst retrospective analyses must always be interpreted with caution, these results suggest that with "best practice therapy", CV risk is lowest at baseline in those patients with the lowest HR. However, when compared to placebo, the addition of nifedipine GITS improved overall outcomes and had no deleterious effects across the quintiles of achieved HR.